Synthesis and characterization of MCM-41 containing CeO2 - Son, Pham Anh; Bang, Nguyen Din; Luong, Ngo Sy (Vietnam Journal of Chemistry, 2014)
MCM-41 and cerium containing MCM-41 mesoporous materials were obtained by hydrothermal method under atmospheric pressure (the molar ratio SiO2/CeO2= x, x = 160, 80, 40, 20). The characteristics of all samples were investigated by ThermoGravimetric - Differential Thermal Analysis (TG-DTA), X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), Energy-Dispersive X-ray spectrometry (EDX) and nitrogen adsorption-desorption isotherms. The results indicated that: particles are sphere, uniform and pore size is about 50 nm; the pore systems are hexagonal structure, ordered arrangement; the samples have high surface area (> 600 m2/g) with narrow pore size distribution curve. Results of EDX showed that the SiO2/CeO2molar ratios of samples were very similar to the molar ratios in gel